A 26-Year-Old Male with Mesothelioma Due to Asbestos Exposure - P. Zarogoulidis; M. Orfanidis; T. C. Constadinidis; E. Eleutheriadou; T. Kontakiotis; T. Kerenidi; L. Sakkas; N. Courcoutsakis; K. Zarogoulidis (Case Reports in Medicine)
Mesothelioma is a malignancy with poor prognosis, with an average 5-year survival rate being less than 9%. This type of cancer is almost exclusively caused by exposure to asbestos. A long exposure can cause mesothelioma and so can short ones, as each exposure is cumulative. We report a case of a 26-year-old male who was exposed to asbestos during his primary school years from the age of 6 to 12. Although the tumor mainly affects older men who in their youth were occupationally exposed to asbestos, malignant mesothelioma can also occur in young adults. A medical history was carefully taken and asbestos exposure was immediately mentioned by the patient. We conducted biopsy on the right supraclavicular lymph node. The patient was not a candidate for surgery, and chemotherapy treatment was initiated. While patient's chemotherapy is still ongoing, no other similar cases of students or teachers have been traced up to date from his school. The school building was demolished in January 2009.